2019
DOI: 10.1186/s11658-019-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-340-5p suppresses non-small cell lung cancer cell growth and metastasis by targeting ZNF503

Abstract: Background MicroRNAs (miRNAs) have been reported to play crucial roles in cancer cell processes, including proliferation, metastasis and cell cycle progression. We aimed to identify miRNAs that could act as suppressors of cell growth and invasion in non-small cell lung cancer (NSCLC). Methods Fifteen paired NSCLC tissue samples and pericarcinomatous normal tissues were collected and preserved in liquid nitrogen. The expression levels of miR-340-5p and ZNF503 mRNA were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Our evidences indicated that miR-340-5p acts as a tumor suppressor in glioma. Those data were in accordance with the previous reports that miR-340 functioned as a tumor suppressor in several cancers, including gastric cancer, breast cancer, squamous cell carcinoma, ovarian cancer, osteosarcoma, multiple myeloma and non-small cell lung cancer [44,45]. In this study, we found that the expressions of LINC00662, STAT3 and STAT3 target genes were downregulated with miR-340-5p OE in U251 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our evidences indicated that miR-340-5p acts as a tumor suppressor in glioma. Those data were in accordance with the previous reports that miR-340 functioned as a tumor suppressor in several cancers, including gastric cancer, breast cancer, squamous cell carcinoma, ovarian cancer, osteosarcoma, multiple myeloma and non-small cell lung cancer [44,45]. In this study, we found that the expressions of LINC00662, STAT3 and STAT3 target genes were downregulated with miR-340-5p OE in U251 cells.…”
Section: Discussionsupporting
confidence: 93%
“…31 Recent evidence suggested that miR-340-5p hindered non-small cell lung cancer progression through degradation of ZNF503. 32 In the current study, ZNF503 was distinctly up-regulated in NSCLC. More importantly, ZNF503 overexpression reversed the inhibitory effect of TTN-AS1 depletion on NSCLC progression.…”
Section: Dovepresssupporting
confidence: 48%
“… Zhou and Li demonstrated that miR‐605 restoration hindered the metastasis of NSCLC . Upregulation of miR‐340 repressed tumor growth and metastasis of NSCLC in the study by Lu and Zhang . Similarly, miR‐150 exhibited an inhibitory effect on the metastasis of NSCLC .…”
Section: Discussionmentioning
confidence: 98%